The Effect of Plant Spacing and Type of Manure on the Growth and Yield of Green Beans (Vigna Radiata L) Cultivar Vima I - Triyanti, Triyanti; Suciaty, Tety; R, Eviyati (Ann Publisher, 2024)
The objectives of this study are: (1) To determine the effect of the combination of planting distance and type of manure on the growth and yield of green bean plants (Vigna radiata L) cultivar VIMA-1, (2) To determine the combination of planting distance and type of manure that can have the best influence on the growth and yield of mung bean plants (Vigna radiata L) VIMA-1 cultivar. The research was conducted in Wirakanan Village, Kandanghour District, Indramayu Regency, from December 2020 to January 2021. The research method used is the Group Random Design (RAK) method. The treatment consists of three levels of planting distance (20x25 cm, 20x30 cm, and 20x35 cm) and three types of manure (chicken, goat, and cow) with a dose of 6 tons/ha for each manure and without manure. The combination is repeated three times so that there are 36 tiles. Variables observed include Plant height, number of leaves, number of pods, weight of 100 grains, weight of dry seeds per plant, and dry weight per plot. The results showed that: (1) the combination of planting distance and type of cow manure significantly affected plant height aged 15, 22, and 29 HST, number of leaves aged 15, 22, and 29 HST, total number of pods, and seed weight per plot. (2) the combination treatment of planting distance and type of manure produces plant height higher is produced by combination D (20x25 cm and cow manure) at the age of 15, 22, and 29 HST, the combination of planting distance and type of manure produces the number of leaves, the higher is produced by the combination of D (20x25 cm and cow manure) at the age of 15, 22 and 29 HST, the combination of planting spacing and type of manure produces the number of pods, the higher one is produced by the combination of D (20x25 cm and cow manure), the combination of planting spacing and type of manure produces the weight of seeds per plot, the higher one is produced by the combination of D (20x25 cm and cow manure). The combination of spacing treatment (20 x 25 cm) and manure (chicken, goat, or cow) at a dose of 6 tons/ha has the best effect on the weight of dry beans per plot, which is 0.64 kg or equivalent to 15.23 quintals/ha (80% effective land).